Evaluating Patients' Knowledge about Lymph Node Cancer and Its Relationship to the Family's Genetic History in the Cancer Center - Iqbal Sahi Tuama; Qassim Jawell Odah Abed; Rana Ali Hameed (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Lymphoma is a type of cancer that begins in the lymphatic system, which is part of the body's immune system. The lymphatic system consists of lymph nodes (lymph nodes), lymph vessels, the spleen, bone marrow, and other organs. Lymphoma occurs when lymphocytes multiply abnormally. Lymphoma is one of the most common cancers, affecting approximately 8 million people worldwide annually. These statistics should not be underestimated, but should be taken into consideration. This study aimed to assess the level of knowledge of patients with lymphoma and to investigate the relationship between family history and risk of developing the disease. A descriptive and analytical cross-sectional study was conducted at a final center in Wasit Governorate, Iraq, from January 2024 to March 2025. Forty patients were included in the study, who were diagnosed with lymphoma and had their lymph nodes sorted. Data were collected through a structured questionnaire covering demographics, family history, and knowledge about the disease. Data were analyzed using SPSS and Excel, with descriptive statistics and chi-square testing applied to determine statistical relationships (at a significance level of ≤ 0.05). The study was conducted using a descriptive analytical approach at the Oncology Center in Wasit Governorate, Iraq, from January 2024 to March 2025. The sample included 40 female patients diagnosed with lymphoma. Data were collected through a structured questionnaire covering demographics, family history, and knowledge about the disease. Data were analyzed using SPSS and Excel, using descriptive statistics and the chi-square test to determine statistical relationships (at a significance level of ≤ 0.05). Most of the participants (61%) had poor knowledge of lymphoma, particularly about its signs and symptoms, risk factors, and preventive measures.